Growth of kiddy shrimp, Parapenaeopsis stylifera(H. Milne Edwards, 1837) along Saurashtra coast - Dineshbabu, A P (Indian Journal of Fisheries, 2011)
Growth of kiddy shrimp, Parapenaeopsis stylifera(H. Milne Edwards, 1837) along Saurashtra coast